Beyond Islamic Finance: Reconstructing Islamic Socioeconomic Thought for Indonesian MSMEs through Decolonial Perspectives - Ahmad Syaichoni; Rifki Sahara (Lan Tabur: JURNAL EKONOMI SYARIAH, 2026)
Indonesia holds the largest Muslim population in the world, yet its Islamic economy remains defined almost entirely through banking and financial industry metrics. Islamic banking assets surpassed IDR 1,050 trillion by early 2026, but market share stayed near 7.5 to 8 percent, a gap that widens further once financial literacy and regulatory barriers facing MSMEs enter the picture. This paper argues that Indonesian Islamic economics suffers from a financialization tendency inherited from its own unexamined epistemological history, one that measures success through asset growth rather than through maqasid al-shariah's original concern with removing harm and drawing benefit at the community level. Using qualitative library research combined with critical discourse analysis, and drawing selectively on prior fieldwork among thirty Muslim MSME producers in Tulungagung Regency, this study builds its argument around four interlocking pillars: decolonial Islamic thought, a reworked reading of maqasid as a socioeconomic ethic rather than a compliance checklist, indigenous Islamic economic practice, and the lived rationality of Indonesian Muslim society. Findings show a persistent disconnect between formal Islamic finance discourse and gotong royong-based economic practice, which survives strongly at the community level but rarely enters policy vocabulary on its own terms except when mined for product design. Fieldwork illustrations, including informal credit extended during Ramadan without a formal contract, demonstrate maqasid functioning directly at the grassroots without institutional mediation. The paper contributes a reorientation toward community-grounded Islamic economic scholarship, treating indigenous practice as primary analytical data rather than an ethnographic supplement, and calls for future empirical work testing this reorientation beyond a single regency.